Clinical Characteristics of Individuals with Interstitial Lung Diseases and Indication of End-of-Life Care - Krinski, Gabriela; Bertin, Larissa Dragonetti; Pimpão, Heloise Angélico; Silva, Humberto; Tavares, Brunna Luiza; Lunardelli, Leonardo; Alves do Prado, Geovana; Pitta, Fabio; Camillo, Carlos Augusto [UNESP] (MDPI, 2023)
End-of-life care (EOLC) is palliative support provided in the last 6 months to 1 year of a patient’s life. Although there are established criteria for its indication, few studies describe the clinical and functional characteristics of individuals with interstitial lung diseases (ILD) in EOLC. ILD individuals underwent various assessments, including lung function, exercise capacity (6 min walk test), physical activity in daily life (PADL), peripheral muscle strength, maximal respiratory pressures, body composition, quality of life (SGRQ-I), symptoms of anxiety and depression, dyspnea (MRC scale), and sleep quality. Fifty-eight individuals were included and divided into two groups according to the indication for commencing EOLC (ILD with an indication of EOLC (ILD-EOLC) or ILD without an indication of EOLC (ILD-nEOLC). There were differences between the groups, respectively, for steps/day (2328 [1134–3130] vs. 5188 [3863–6514] n/day, p = 0.001), time spent/day carrying out moderate-to-vigorous physical activities (1 [0.4–1] vs. 10 [3–19] min/day, p = 0.0003), time spent/day in standing (3.8 [3.2–4.5] vs. 4.8 [4.1–6.7] h/day, p = 0.005), and lying positions (5.7 [5.3–6.9] vs. 4.2 [3.6–5.1] h/day, p = 0.0004), the sit-to-stand test (20 ± 4 vs. 26 ± 7 reps, p = 0.01), 4 m gait speed (0.92 ± 0.21 vs. 1.05 ± 0.15 m/s, p = 0.02), quadriceps muscle strength (237 [211–303] vs. 319 [261–446] N, p = 0.005), SGRQ-I (71 ± 15 vs. 50 ± 20 pts, p = 0.0009), and MRC (4 [3–5] vs. 2 [2–3] pts, p = 0.001). ILD individuals with criteria for commencing EOLC exhibit reduced PADL, functional performance, peripheral muscle strength, quality of life, and increased dyspnea.
Keywords: end-of-life care; interstitial lung diseases; palliative care